Green philanthropy: Islamic activism on Indonesia’s environmental democracy - Humaidi, M. Wildan; Hariyanto, Hariyanto; Azizah, Mabarroh (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2024)
Through the mechanisms of zakat, alms, and waqf, Islam is constructed as a philanthropic religion. The practice of philanthropy has been institutionalised as a religious social institution through the institution of amil zakat, infaq, and sedekah (LAZIS). Over time, the distribution patterns of Islamic philanthropic institutions have evolved, shifting from a focus on economic empowerment and religious da’wah to an emphasis on sustainable development and environmental issues, a concept referred to as “Green Philanthropy”. This research employs empirical methods using qualitative approaches. The data is derived from the practices of various philanthropic organisations in Banyumas Indonesia, such as Dompet Dhuafa, LAZIS Muhammadiyah (LAZISMU), and LAZIS Nahdlatul Ulama (LAZISNU), serving as primary data, alongside various relevant literature as secondary data. This research aims to explore the practices and dynamics of philanthropic distribution that contribute to environmental conservation programs. Employing a phenomenological framework, this study explores the dynamics and practices of Islamic philanthropic institutions in implementing various environmental conservation programs and achieving benefits oriented towards sustainable development. This practice evolved into a significant activism movement advocating for environmental sustainability driven by various Islamic philanthropic organisations. Consequently, this movement reflects efforts to enhance environmental democracy in Indonesia through the engagement of diverser societal elements in environmental conservation and sustainable development programs. As an academic contribution, this research reveals the role and involvement of Islamic philanthropic institutions in efforts to preserve the environment and achieve sustainable development. The practice of philanthropy is a dynamic phenomenon within Islamic law and Muslim activism in response to global challenges.